Efficacy and safety of tazemetostat, an EZH2 inhibitor, in Chinese patients with relapsed/refractory follicular lymphoma: a multicentre, single-arm, phase 2 studyResearch in context - Junning Cao; Guangliang Chen; Lihua Qiu; Liling Zhang; Ming Jiang; Ying Cheng; Qiaohua Zhang; Lihong Liu; Ping Li; Yuerong Shuang; Huaqing Wang; Hongwei Xue; et al. (EClinicalMedicine)
Summary: Background: Tazemetostat, the first enhancer of zeste homolog 2 (EZH2) inhibitor approved by the U.S. Food and Drug Administration, has shown efficacy in a global population with relapsed or refractory (R/R) follicular lymphoma (FL). This phase 2 study was primarily designed as a registration-intent bridging trial of tazemetostat in Chinese patients with EZH2-mutant (EZH2mut) R/R FL; the study also included evaluation in the EZH2 wild-type (EZH2wt) population. Methods: This multicentre, single-arm, phase 2 study was conducted at 19 sites in China. Eligible patients (aged ≥18 years) with histologically confirmed grade 1–3a FL were categorised by EZH2 status: mutant (EZH2mut, bridging cohort) and wild-type (EZH2wt), and received oral tazemetostat 800 mg twice daily in continuous 28-day cycles until investigator-assessed disease progression, intolerable toxicity, withdrawal of consent, or other protocol-specified criteria. The EZH2mut cohort primary endpoint was independent review committee (IRC)-assessed objective response rate (ORR). Efficacy in the EZH2mut cohort was assessed in patients who received at least one dose of tazemetostat and had centrally confirmed FL. Efficacy in the EZH2wt cohort and safety in both cohorts were assessed in all patients who received at least one dose of tazemetostat. This study is registered with ClinicalTrials.gov, NCT05467943. Findings: Between July 29, 2022, and Aug 31, 2023, 22 patients with EZH2mut R/R FL were enrolled (three lines [3L] of prior therapy, 31.8%; four lines [4L] of prior therapy or more, 27.3%). As of Aug 31, 2024 (median follow-up 14.4 months), IRC-assessed ORR was 63.6% (95% confidence interval [CI], 40.7%–82.8%), clinical benefit rate (CBR) was 90.9% (70.8%–98.9%), median duration of response (DoR) was not reached (18-month DoR rate, 51.6% [18.2%–77.3%]), and median progression-free survival was 15.4 (8.2–not estimable) months. All patients experienced treatment-related adverse events (TRAEs), and 13.6% had grade ≥3 TRAEs; most common TRAEs were haematological toxicities. For the EZH2wt cohort, 20 patients were enrolled (3L, 35.0%; ≥4L, 45.0%). Tazemetostat also demonstrated efficacy benefit and a manageable safety profile in the EZH2wt cohort, with an investigator-assessed ORR of 35.0% (95% CI, 15.4%–59.2%), CBR of 85.0% (62.1%–96.8%), and median DoR of 8.4 (1.9–15.7) months. Interpretation: These results suggest that tazemetostat has a clinically meaningful efficacy and was well tolerated in Chinese patients with R/R FL. Larger trials are warranted. A multicentre, randomised, phase 3 trial of tazemetostat combined with lenalidomide plus rituximab vs. lenalidomide plus rituximab in patients with R/R FL is ongoing (NCT04224493). Funding: HUTCHMED.